Determinants of productivity growth: Science and technology policies and the contribution of R&D - Catherine Duverger; Bruno van Pottelsberghe de la Potterie (EIB Papers, 2011)
This paper provides an update of the paper From R&D to Productivity Growth: Do the Institutional Settings and the Source of Funds of R&D Matter? (Guellec and van Pottelsberghe 2004). We present estimates of the long-term impact of various sources of knowledge (R&D performed by the business sector, the public sector (higher education and government) and abroad) on the multifactor productivity growth of 17 major OECD countries from 1988 to 2006. The results confirm that business R&D and the R&D performed by the higher education sector significantly contribute to growth. In addition, the extent to which countries rely on triadic patents, as well as their degree of patent friendliness (enforcement mechanism and number of restrictions) affect significantly the extent to which R&D contributes to growth.
Keywords: 330; Industrielle Forschung; Bildungspolitik; Öffentliche Bildungsausgaben; Produktivität; Patentrecht; OECD-Staaten